Female Board Independency in Corporate Governance and Firm Performance - Sephia Septiana; Robin Robin; Yulfiswandi Yulfiswandi (LPPM Universitas Terbuka, 2022)
Purpose – This research examines female board independence and influence on company performance. The concept of female leaders in work should be discussed since gender inequality assumes that they are considered not socially accepted, have a non-business background, and are appointed due to nepotism. Methodology – The research uses a quantitative approach - research data from companies listed on the Indonesia Stock Exchange in the KOMPAS100 index from August 2021 to January 2022. The data was collected from the company’s financial reports from 2014 to 2020. Findings – It was found that both Tobin’s Q and ROA were significantly negative for female board independency. It reduces the effectiveness of a company’s profitability. Females are considered incompetent since they were appointed for family ties and not based on skills or qualifications. The robustness test reveals that the female board independence dummy test with Tobin’s Q and ROA is considerably negative. Furthermore, female board members do not affect the company’s success or ability to persuade investors. Originality – Females are discouraged from serving as independent members to avoid harmful performance impacts. Therefore, the idea of considering them as members of the board of independence should be discouraged, as it will affect the opinions of investors.